Helping students understand the text through scaffolding - Deni Sapta Nugraha (Journal on English as a Foreign Language, 2015)
This study reported the practice of helping adult students to comprehend the texts in Indonesian Civil Aviation Institute majoring at Air traffic controller programme, Curug - Tangerang. The article demonstrated of how teacher helped them to comprehend the text during 100 minutes reading class in three meetings. It was employed as their input session to acquire context, knowledge and specific vocabulary in aviation or what so called as phraseology. Students were asked to construct some questions dealing with the text both literal and inferential comprehension suggested by Barrett (in Eanes 1997). The result showed that students attained three main bonuses; they get used to build questions that impact to their grammatical awareness, they get used to communicate orally, and they are successful to comprehend the text thoroughly by acquiring new knowledge, vocabulary as well as context.